Evaluation of a new transportation container for red cell units in Western Australia. (7th October 2015) - Grey, D. E.; Fong, E. A.; Soares Mendes, R.; Gilhooley, G.; Cardey, J.; Finlayson, J.
Abstract : Background and Objectives: Extremes of weather, temperatures above 50°C and large distances to transport blood necessitate a robust container that is simple to pack and maintains the internal control temperature for long periods. We describe the evaluation and implementation of a new blood transport container, PX3L‐Universal Courier AcuTemp (CSafe Global, USA), throughout Western Australia. Materials and Methods: The new transport container was initially validated to maintain two or four units of red cells at an internal control temperature of 2–10°C using simulated external ambient temperatures. Subsequent validation studies assessed real‐time external ambient temperatures involving transportation around Western Australia for a distance of 25 360 km. Prior to implementation, staff were trained by e‐learning and real‐time packing. Four months of postimplementation data (October 1 2014 to February 6 2015) were reviewed. Results: The new container is light (6·18 kg) and easy to pack using a single refrigerator belt that protects the red cell units from the freezer belt. It will maintain two or four red cell units at an internal control temperature of 2–10°C for up to 70 h. During the 4‐month utilization period, 547 red cell units were transported to 36 different sites and only three were outside the target of 2–10°C due to failure to follow protocol. Conclusion: The PX3L‐Universal Courier AcuTemp (CSafe Global, USA) blood transportation container was found to be simple to assemble, lightweight and maintained the required internal control temperature for the necessary transport time. This will preserve product quality, ensure patient safety and greatly assist in minimization of red cell wastage.